Kimura's disease and ankylosing spondylitis: A case report. Issue 34 (21st August 2020) - Chen, Anping; Cui, Beibei; Li, Yanhong; Zhang, Qiuping; Yuan, Mingqi; Liu, Yi
Abstract: Rationale: Ankylosing spondylitis (AS) and Kimura's disease (KD) which is quite rare are both chronic inflammatory diseases. Recently we encountered a patient who suffered from KD and AS, and some of his family members also suffer from AS. We, therefore, investigated this unique case and conducted the family-based whole exome sequencing to explore the possible genetic alterations. Patient concerns: Here, we reported a case of a 44-year-old Chinese man with multiple painless masses all over his body and a back pain for 32 years. His uncle and sister were diagnosed with AS. Diagnosis: The diagnosis of KD was based on the patient's clinical features and the biopsy of the neck masses. The diagnosis of AS was based on the patient's clinical features, HLA-B27(+) and the radiologic changes of sacroiliac joints. The genetic test showed that ARPC1B gene which was associated with recurrent infections, auto-inflammatory changes and elevated IgE levels was mutated in this patient. Interventions: Neck masses were removed by surgery. Systemic glucocorticoid, nonsteroidal anti-inflammatory agents, combined with cyclosporine were orally administered, and Etanercept was injected subcutaneously. Outcomes: The masses disappeared rapidly after surgery combined with systemic glucocorticoid, but relapsed shortly after the therapy was discontinued. Low dose glucocorticoid, cyclosporine and Etanercept could keep both KD and AS remained long-term remission. Lessons: Our experience suggests that low dose glucocorticoid, cyclosporine and Etanercept could be beneficial for the patient with KD and AS. The mutation of ARPC1B gene in this case, which is associated with immunologic disturbance, may increase the susceptibility of KD.